ARMENIA: THE CRISIS AND FUNDAMENTAL ECONOMIC PROBLEMS - KHACHATRIAN, Haroutiun (CENTRAL ASIA AND THE CAUCASUS, 2009)
The world crisis interrupted the stable economic growth Armenia had been enjoying for the past fifteen years. Progressive development began in 1994, whereby between 2001 and 2007 the growth indices reached double digits. In 2008, the increase in GDP came to a halt due to the Russian-Georgian war and amounted to only 6.8%.1 And as early as the first six months of 2009, the GDP began to decrease, dropping as low as 16.3% compared to the same period of the previous year, which is one of the worst indices for the entire CIS.2 In July, the drop in GDP amounted to 18.7%, which encouraged people to think that the crisis had bottomed out. The Armenian government took measures that reduced the negative impact of the crisis to a minimum. This was mainly assisted by financial aid from the outside. However, both independent observers and government representatives admit that the crisis only aggravated the problems that already existed in the country’s economy. While there are others who believe that the crisis will be conducive to radical restructuring that will make the economy more efficient and competitive. From the very beginning, it was clear that Armenia, with its small domestic market, would be dealt a severe blow by the crisis that began beyond its borders since it was bound to affect the countries to which the republic exports goods and services and which make investments in Armenia. Nonferrous metals (copper, molybdenum, and aluminum) constitute about half of Armenia’s export. In recent years, the pricing environment has been shaping up favorably, and the export earnings have noticeably grown. But it was obvious that the crisis threatened a cutback in the consumption of nonferrous metals and a drop in prices, particularly for copper, which is used in large amounts in construction. It is worth recalling that it was precisely a decline in construction that triggered the world crisis. The export of manpower is another important article of Armenia’s revenue. After the collapse of the U.S.S.R., between 600,000 and 800,000 Armenians (15-20% of the population), according to some sources, left the country in search of a way to earn a living. Approximately 60,000 periodically leave to work at seasonal jobs. It goes without saying that the remittances labor migrants and members of the Armenian diaspora send to their relatives in Armenia constitute the republic’s revenue from this “export.” In 2008, the noncommercial bank transfers amounted to 1 billion 630 million, which is more than 10% of GDP and almost 48% of the domestic trade turnover.